2014
DOI: 10.1017/s1479591413000181
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Islam in Indonesia: How Television Producers Mediate Religiosity Among National Audiences

Abstract: While Indonesia's burgeoning private television industry has prospered through the country's democratic transition and the rise of popular Islam, it has remained ideologically constrained by many of the content restrictions established during Suharto's New Order era. One area in which producers have broken these norms is in the field of religious imagery, and the adaptation of religiously-themed narratives and tropes. This articlebased on a long-term ethnographic study of television producers in Indonesia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Since the advent of popular, commercial Islam in the late 1990s, however, Christian‐oriented production houses, and later regional television stations, have been gaining a gradual if lower profile within the industry. Whereas I have previously argued (Barkin , in press) that most programming that caters explicitly to Muslim audiences represents a commercial Islam aimed at mobilizing religious sentiment within a neoliberal field, broadcasting in Christian‐majority North Sulawesi illustrates what I argue to be an ideologically distinct approach to religious identity construction rooted in the charged subjectivity of a persecuted minority group eager to elevate itself above the religious and political norms of the ambient, national mediascape. Here, I examine the case of one such regional TV station in an effort to illuminate recent changes in the production culture of regional broadcasters among Indonesia's Christian populations.…”
Section: The Rise Of Regional Televisionmentioning
confidence: 87%
See 2 more Smart Citations
“…Since the advent of popular, commercial Islam in the late 1990s, however, Christian‐oriented production houses, and later regional television stations, have been gaining a gradual if lower profile within the industry. Whereas I have previously argued (Barkin , in press) that most programming that caters explicitly to Muslim audiences represents a commercial Islam aimed at mobilizing religious sentiment within a neoliberal field, broadcasting in Christian‐majority North Sulawesi illustrates what I argue to be an ideologically distinct approach to religious identity construction rooted in the charged subjectivity of a persecuted minority group eager to elevate itself above the religious and political norms of the ambient, national mediascape. Here, I examine the case of one such regional TV station in an effort to illuminate recent changes in the production culture of regional broadcasters among Indonesia's Christian populations.…”
Section: The Rise Of Regional Televisionmentioning
confidence: 87%
“…Kitley ), as discussion and representation of previously forbidden topics no longer threatened TV stations with closure or disciplinary action . I came to focus on the transformation of religious programming, and in particular the burgeoning of a discursively commercial Islam that endeavored to represent religious themes in ways that comported with national citizenship and neoliberal subjectivities (Barkin in press). As with Abu‐Lughod's () work on Egyptian TV and Mankekar's () discussion of the Ramayana TV series in India, these changes have come to fuse the country's dominant religion with conceptions of national citizenship in such a way as to sideline religious minorities, and in this case challenge their “Indonesianness.” My initial goal for this project was to explore what might be characterized as reactions to these broad sociopolitical and mediacentric changes from the country's margins, where Christian minorities have exploited a relaxation of broadcast regulations in the past decade to form distinctive and insular mediascapes within the larger field of Indonesian media cultural production (Bourdieu ).…”
Section: The Rise Of Regional Televisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering the vast majority of the audience is Muslim, the messages of Islamic teaching are part of the important contents of the media. Barkin (2014), for instance, observed that Indonesian private television producers were successful in taking advantage of Muslim viewers to commercialize Islam. Despite a number of criticisms that they are facing (Barkin 2014), the media continues to present Islamic messages through television to attract viewers.…”
Section: Islam and Mediamentioning
confidence: 99%
“…Barkin (2014), for instance, observes that Indonesian private television producers were successful in taking the advantage of Muslim viewers to commercializeIslam. Despite a number of criticisms that they are facing(Barkin, 2014), the media continue to present Islamic messages through television to attract viewers. a piece of information is a hoax.…”
mentioning
confidence: 99%